Well, this kind of question asks for your intuitive understanding of temporal logic formulas. You should first read and understand the formulas to then point out their differences.
In your example, you can first understand that S2 implies S1, which means that
((F c) -> (X a)) -> ((X c) -> (F a))
is valid. Why is that so? By propositional logic, (a->(b->c)) is equivalent to (a&b)->c, thus, the formula is equivalent to
(X c) & ((F c) -> (X a)) -> (F a)
which is valid: if (X c) holds, then also (F c) holds, and by modus ponens, it then follows also that (X a) must hold, and that in turn implies (F a).
Hence, S2 implies S1 and we must therefore search for counterexamples for S1->S2, since there are no counterexamples for S2->S1. A counterexample for S1->S2 is an example for S1&!S2, thus an example for
((X c) -> (F a)) & (F c) & !(X a)
Hence, find an example where once c holds, a does not hold at the next point of time, and if c should hold at the next point of time, then a should hold at some point of time.
For example, you could use any path that satisfies
c & (X !a) & (X !c)
since
(c & (X !a) & (X !c)) -> ((X c) -> (F a)) & (F c) & !(X a)
But you can also make X c true which must then also make a true at least once, but not at the next point of time. For example, you can choose any path that satisfies
(a & !c) & X(!a&c)
Question 2): If G(!a&b) holds, then we have always have [b WU a] and therefore also [c WU [b WU a]] but it is not needed to demand that !c holds initially.
Question 3) There is no special trick, you just have to additionally make sure that your first formula is not equivalent to the second one.